1984
DOI: 10.1111/j.1399-6576.1984.tb02086.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Time Course During Weaning from Respirator Treatment

Abstract: Ten patients who developed disturbed mental function during respirator weaning were studied. They were investigated during respirator treatment and 1 h after start of spontaneous ventilation with continuous reaction time measurements and clinical ratings. During the spontaneous ventilation the reaction times increased and the patients experienced fatigue. PaCO2 was higher and PaO2 was lower than during respirator treatment. A significant correlation was found between individual differences of reaction times an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This task has been widely used to study the effects of stressors and drugs [Broadbent, 1971]. Continous reaction time has been shown to be impaired by other forms of physical illness [Elsass and Christensen, 1984] and in one study [Elsass and Henriksen, 1984] it was found that the performance impair ment preceded the clinical symptoms. It was predicted that the task used here would be impaired by colds because it involved rapid movements of the hand.…”
Section: Introductionmentioning
confidence: 99%
“…This task has been widely used to study the effects of stressors and drugs [Broadbent, 1971]. Continous reaction time has been shown to be impaired by other forms of physical illness [Elsass and Christensen, 1984] and in one study [Elsass and Henriksen, 1984] it was found that the performance impair ment preceded the clinical symptoms. It was predicted that the task used here would be impaired by colds because it involved rapid movements of the hand.…”
Section: Introductionmentioning
confidence: 99%